A personal journey with matrix metalloproteinases - Nagase, H (De Gruyter, 2016)
I was given the honor of delivering the 2015 Lifetime Membership Award lecture at the International Proteolysis Society's annual meeting held in Penang, Malaysia in October 2015. It gave me an opportunity to look back on how I started my research on matrix metalloproteinases (MMPs) and how I continued to work on these proteinases for the next 42 years. This is a series of sketches from the personal journey that I took with MMPs, starting from the purification of metalloproteinases, cloning, structural studies, then to a more recent encounter, endocytic regulation of matrix-degrading metalloproteinases.